Perceptions of Belongingness in Stem Subjects and Career Development for Middle School African American Girls - (:unkn) unknown (My University, 2017)
This study addresses the hypothesis that African American girls’ early perceptions of support in middle school influences their narrowing or broadening of interest in STEM (Science, Technology, Engineering, Mathematics) subjects and careers. As previously researched the belief that boys excel at math and science while girls do well in the humanities is not supported by findings. Therefore the purpose of this study is to investigate the interaction of contextual factors such as teacher, parent, and peer support for African American middle school girls and their interest in STEM subjects utilizing a qualitative research method. Students are making decisions about their careers as early as middle school and lack exposure to the career possibilities in the STEM fields and therefore may be making decisions about career choices without accurate information. Math and science teachers are critically important in early STEM- related career interest development and equally important is students' perceptions of support and feelings of belongingness within their various settings.
Keywords: Belongingness; Middle School; STEM